PENGUATAN INTEGRASI NASIONAL MELALUI PENERAPAN NILAI-NILAI PANCASILA DALAM KEHIDUPAN BERBANGSA - Anindita, Giezka Khaleda; Hidayati, Nurul (Padma Sari: Jurnal Ilmu Pendidikan, 2025)
As an archipelago, Indonesia has a diversity of cultures, religions, and ethnicities that are both an advantage and a challenge in strengthening national integration. In the midst of increasingly rapid globalization, the implementation of Pancasila values is the main foundation for maintaining national unity. This research aims to analyze how the values of Pancasila can be applied to strengthen national integration in Indonesia. This article uses a literature study method where researchers review several articles on the Google Scholar page that are relevant to the topic. This research explains that the values contained in Pancasila need to be instilled early on by the community to face challenges and maintain national integration in diversity. The results show that the value of Belief in One God can foster tolerance between religious communities, the value of Fair and Civilized Humanity encourages empathy and respect for human rights, while Indonesian Unity is the basis for strengthening national identity. The values of Democracy and Social Justice encourage active community participation in the life of the nation and state in an inclusive manner. Several empirical studies have shown that strengthening these values through Pancasila education in schools, diversity training, and social media can increase collective awareness of the importance of national integration. The main contribution of this research is to provide conceptual and practical understanding of the implementation strategy of Pancasila values in the contemporary socio-political context of Indonesia, so that it can be used as a reference in education policy and sustainable national character building.